Growing Up in the Mine: Unpacking Structural and Familial Drivers of Child Labor in Kenya’s Small-Scale Mining Sector - George Ochieng Okello; Taji Isindu Shivachi; Michael Ntabo Mabururu (African Journal of Education,Science and Technology (AJEST), 2025)
This paper explores the structural and familial dynamics that shape child labor in artisanal and small-scale gold mining (ASGM) communities in Kenya, with a focus on Nyatike and Rongo Sub-Counties. While poverty, weak policy enforcement, and limited access to education are commonly cited macro-level causes of child labor, this study highlights how deeply embedded micro-level factors—such as family instability, intergenerational labor norms, and community expectations—contribute to children’s participation in mining work. Drawing on Bronfenbrenner’s Ecological Systems Theory, the research examines how interactions across the microsystem (e.g., family transitions like divorce or migration), exosystem (e.g., informal mining economies), and macrosystem (e.g., cultural norms on childhood and labor) collectively reinforce children’s engagement in hazardous labor. The chronosystem further helps explain how the timing of familial disruptions and life transitions increases children’s vulnerability at specific developmental stages. Using qualitative data from interviews and focus group discussions with children, caregivers, community leaders, and local stakeholders, the study reveals that child labor in mining is often not viewed as a crisis but as a normalized survival strategy. Children are socialized into labor by caregivers and peers, and their work is frequently framed as a contribution to family welfare amid precarious livelihoods. Agency Theory is applied as a complementary lens to understand how children and families, within constrained environments, make calculated decisions that prioritize immediate survival over long-term aspirations like schooling. The findings call for holistic interventions that address not only economic deprivation but also the hidden relational, cultural, and institutional dimensions that sustain child labor. By foregrounding the everyday realities of mining communities, the study challenges dominant narratives of victimhood and instead highlights the complexity of children’s labor trajectories.